2012
DOI: 10.3747/pdi.2011.00137
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Initial Peritoneal Transport Characteristics, Inflammation, and High Glucose Exposure on Prognosis for Peritoneal Membrane Function

Abstract: ♦ BackgroundFast transport status, acquired with time on peritoneal dialysis (PD), is a pathology induced by peritoneal exposure to bioincompatible solutions. Fast transport has important clinical consequences and should be prevented.♦ ObjectiveWe analyzed the repercussions of initial peritoneal transport characteristics on the prognosis for peritoneal membrane function, and also whether the influence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…Small solute transport rates showed a simultaneous regression to mean values, increasing in slower transporters and decreasing in fast transporters. Similar findings were reported by Fernandez-Reyes et al (13), with nonsignificant trends to an increase in UF during the first year, and a later progressive decay. A more recent in-depth study (14), based on SPA tests, partially confirmed the results of previous investigations, by reporting an overall stability of the capacity of UF during the first years, followed by a later decline, particularly after the fourth year on PD.…”
Section: Discussionsupporting
confidence: 91%
“…Small solute transport rates showed a simultaneous regression to mean values, increasing in slower transporters and decreasing in fast transporters. Similar findings were reported by Fernandez-Reyes et al (13), with nonsignificant trends to an increase in UF during the first year, and a later progressive decay. A more recent in-depth study (14), based on SPA tests, partially confirmed the results of previous investigations, by reporting an overall stability of the capacity of UF during the first years, followed by a later decline, particularly after the fourth year on PD.…”
Section: Discussionsupporting
confidence: 91%
“…Last, APD is usually the modality of choice for the treatment of high transporters in PD. It is known that these patients are at high risk for ultrafiltration failure and present significantly more comorbidities that may influence outcomes, particularly when glucose-sparing solutions are not available, as was our case at the time (21,22).…”
Section: Technique Survival: Main Findings and Predictorsmentioning
confidence: 58%
“…It has long been recognized that there is a large variability in the characteristics of water and solute transport across the peritoneal membrane and that in some individuals, these conditions change over time [16][17][18][19]. This variability may have important clinical consequences, and monitoring these parameters is essential, to guide prescription and improve patient outcomes [20].…”
Section: Discussionmentioning
confidence: 99%